Fixed Point Results for Almost Generalized Cyclic (ψ,φ)-Weak Contractive Type Mappings with Applications - Mohamed Jleli; Erdal Karapınar; Bessem Samet (Abstract and Applied Analysis)
We define a class of almost generalized cyclic (ψ,ϕ)-weak contractive mappings and discuss the existence and uniqueness of fixed points for such mappings. We present some examples to illustrate our results. Moreover, we state some applications of our main results in nonlinear integral equations.